Change of direction ability in young elite soccer players: determining factors vary with angle variation - Rouissi, M.; Chtara, M.; Owen, A.; Burnett, A.; Chamari, K. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The ability to change direction is considered of paramount importance in team sports. Currently there is a lack of consensus regarding the most important physical factors that determine change of direction (COD) ability. Therefore, the aim of this study was to examine the relationship between COD ability and targeted selected physical attributes of sprinting, isometric strength and explosive power.